The Role of Financial Inclusion, Digital Marketing, and Fintech in Driving Msme Sustainability Toward an Inclusive and Competitive National Economy - Febriani, Nova; Rahel, Herlina Kristin; Putri, Ressalyu Melani; Maulinda, Chiara (Keizai, 2025)
This study aims to examine the effect of financial inclusion, digital marketing, and financial technology (fintech) on the sustainability of Micro, Small, and Medium Enterprises (MSMEs). The research involved a sample of 72 MSMEs in Sampit City, selected using the convenience sampling method. The data were analyzed using multiple linear regression. The findings indicate that financial inclusion, digital marketing, and fintech have a positive influence on MSME sustainability. Improved access to formal financial services enables MSMEs to obtain more equitable sources of financing, thereby expanding economic opportunities for entrepreneurs across different social groups. The utilization of digital marketing and fintech further accelerates the digital transformation of MSMEs, enhances productivity, broadens market reach, and strengthens the competitiveness of local products at both national and global levels. Ultimately, the reinforcement of these three aspects not only contributes to the sustainability of individual enterprises but also fosters the development of a more inclusive economic ecosystem, adaptive to technological advancements and capable of supporting sustainable economic growth.